Outliving the outbreak: how the landscape architecture profession can address bark beetle impacts in the Rocky Mountain region - Hodgson, Danielle (Kansas State University, 2020)
Bark beetles have played a fundamental role in coniferous ecosystems for thousands of years but have recently reached unprecedented levels of reproduction and infestation within the Rocky Mountain region (Oatman 2015, Bentz 2009). In Colorado alone, mountain pine beetles and spruce beetles have killed 21% of Colorado’s forests since 1996 (Romeo 2019). Concurrent outbreaks, extended north and east range, and longer lifespans of bark beetles have contributed to more significant infestations that are primarily a result of increasing temperatures and less regional precipitation (Bentz 2009). Mountain-based industries such as skiing, tourism, and recreation are threatened by loss of tree stands and potential fire danger (Prestemon et al. 2013; Frost 2009; Wells 2005). With the increasing visual and physical impacts of bark beetles on mountain ecosystems, landscape architects will need to understand how to respond to these impacts within the natural and built environments. Management applications on infected stands will impact the aesthetic value of coniferous forests, which can have negative influences on visitor perceptions (Arnberger et al. 2018). This report documents the projected extent and significance of existing bark beetle outbreaks relative to historical trends/events and the degree to which landscapes are impacted by the loss of scenic value following bark beetle outbreaks. This report uses previous outbreaks to evaluate future scenarios of bark beetle impacts to address the potential threats to mountain ecosystems and implications on human experiences. Guidelines were then generated based on landscape management techniques of bark beetle, such as promoting biodiversity and reducing even-aged tree stands, as well as applying principles of landscape aesthetics (Bentz 2009). The goal of this report is to encourage discussions within the landscape architecture community to ensure a balance between the sustainable environmental treatment of bark beetle infestations and preservation of both visual and cultural value of infested forests.
Keywords: Bark beetles; Landscape architecture; Landscape aesthetics; Mountain pine beetle; Spruce beetle